PERLINDUNGAN KONSUMEN DALAM UPAYA PENGAJUAN GANTI KERUGIAN ATAS PENIPUAN JUAL BELI PONSEL ILEGAL PADA TRANSAKSI ELEKTRONIK MELALUI E-COMMERCE - Ida Bagus Ariadi Rahadita; Si Ngurah Ardhya; Komang Febrinayanti Dantes (Universitas Pendidikan Ganesha, 2023)
This research aims to find out, analyze and examine (1) the legal basis that can be used as a basis for consumer protection in the compensation process (2) legal remedies that consumers can take if compensation is refused. In order to answer the problem formulation in this research, a normative legal research method was used, namely research carried out by examining library materials and secondary data regarding analysis from a legal perspective of Law No. 8 of 1999 concerning Consumer Protection. In relation to the type of research used, namely normative legal research, the approaches used are the statutory approach and the case approach. The technique for collecting legal materials in this research was carried out through literature research techniques, which were carried out to obtain materials and information that were relevant to the case being discussed. (1) that in electronic transactions business actors are obliged to provide correct information regarding goods being bought and sold so that there is no loss to both parties (2) that there is no responsibility by business actors for losses suffered by consumers in accordance with the provisions of Article 27 letter a of the Law -Law No. 8 of 1999 concerning Consumer Protection which is used as the basis for refusing responsibility by business actors.